2011
DOI: 10.3378/027.083.0104
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA in Basque Descendants from the City of Trinidad, Uruguay: Uruguayan- or Basque-like Population?

Abstract: Like other countries in the Americas, during its colonization Uruguay was the recipient of immigrants from several ethnic groups from Europe, as well as of enslaved Africans. After its independence in 1830, Basques were the first group of Europeans to arrive in the country. In this paper, we aim to contribute to the understanding of the process of integration of these migratory waves into the Uruguayan society. For that purpose, individuals of Basque origin from the city of Trinidad, Uruguay, were chosen to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 58 publications
(45 reference statements)
1
23
0
8
Order By: Relevance
“…Five contemporary individuals living in different parts of Uruguay carry the lineage described in this paper: one in Cerro Largo in the northeast, one in Rocha in the east, one in Trinidad and one in Soriano, both in the west, and one in Montevideo in the south Pagano et al 2005;Sans et al 2006Sans et al , 2011. Considering that the total sample analyzed was composed by 728 individuals, and that the novel C1d lineage comprised 0.7%, the rough equivalent in the present-day Uruguayan population would amount to 5,500 individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five contemporary individuals living in different parts of Uruguay carry the lineage described in this paper: one in Cerro Largo in the northeast, one in Rocha in the east, one in Trinidad and one in Soriano, both in the west, and one in Montevideo in the south Pagano et al 2005;Sans et al 2006Sans et al , 2011. Considering that the total sample analyzed was composed by 728 individuals, and that the novel C1d lineage comprised 0.7%, the rough equivalent in the present-day Uruguayan population would amount to 5,500 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…One contemporary individual, part of our study about Basque-descendants in Trinidad, is identified as sample B11 , was selected for analysis of the whole mtDNA genome. We employed sets of primers previously used by our laboratory (Handt et al 1996;Martínez-Cruzado et al 2005;Sans et al 2011;Vigilant et al 1989), which were complemented with primers designed by Rieder et al (1998), and three others designed by us (see Table 2 for details on the primers). The 27 overlapping fragments were purified using silica columns, and sent for sequencing to the Institut Pasteur, Montevideo, Uruguay.…”
Section: Dna Extraction and Analysesmentioning
confidence: 99%
“…The partial sequences compiled from the literature (Supplemental Table S3) revealed more information on the ethnic origin of the donors: Potential D1g samples have been reported in Argentinean Mapuche (Ginther et al 1993); in three native Chilean populations (Moraga et al 2000), namely, Mapuche, Pehuenche Mapuche, and Yaghan/Yamana; and in (19th Century) skeletal remains of the Kaweskar and Yaghan/Yamana from Tierra del Fuego (García-Bour et al 2004). Haplogroup D1j was matched by sequences obtained from Argentinean Mapuche (Ginther et al 1993 Lalueza-Fox et al 2001;Tajima et al 2004), as well as African Brazilian (Carvalho et al 2008) and self-identified Basque descendants from Uruguay (Sans et al 2011), revealing maternal admixture in the latter two.…”
Section: The Mtdna Legacy Of the Mapuchementioning
confidence: 98%
“…To better evaluate the geographical distribution of the novel haplogroups, we surveyed published and unpublished CR data from a wide range of populations (Ginther et al 1993;Horai et al 1993;Alves-Silva et al 2000;Moraga et al 2000;Lalueza-Fox et al 2001;García-Bour et al 2004;Tajima et al 2004;Cabana et al 2006;Á lvarez-Iglesias et al 2007;Tamm et al 2007;Carvalho et al 2008;Salas et al 2008;Bobillo et al 2010;Catelli et al 2011;Gayà-Vidal et al 2011;Prieto et al 2011;Sans et al 2011;MC Bobillo, unpubl.). This allowed the identification of 103 putative D1g and D1j mtDNAs (Supplemental Table S3).…”
Section: Phylogeographic Patterns Of D1g and D1jmentioning
confidence: 99%
“…Previous research has shown that the Uruguayan population has a particular genetic behavior; in addition to its small size (three millions inhabitants), it presents such a high level of miscegenation that there are individuals that cannot currently identify their ancestors' origin. It has a tri-hybrid origin (Caucasoid, African and Amerindian) but, unlike other Latin-American countries, we do not isolate Amerindian groups Gascue et al, 2005;Mimbacas et al, 2003Mimbacas et al, , 2004Mimbacas et al, , 2007Mimbacas et al, , 2009Sans et al, 2011). Thus, this would permit us to think a priori that ethnological factors would (at least in part) cancel each other, therefore eliminating their possible blurring effect on the analysis.…”
Section: Miscegenated Populationmentioning
confidence: 90%